Control strategy of DC/DC converter for photovoltaic-storage-DC microgrid based on improved LADRC. Issue 1 (1st June 2022) - Liu, Fengyi; Guo, Kunli; Hao, Yifan; Cai, Weizheng; Li, Bohao; Lv, Jiajun; Liu, Luhao
Abstract: Aiming at the problem that the DC bus voltage is easily affected by nonlinear noise of the converter, photovoltaic output power and load disturbance, a bidirectional DC/DC converter control strategy based on the improved Linear Active Disturbance Rejection Control is designed. Firstly, establish the mathematical model of the bidirectional DC/DC converter, and analysis of existing problems in traditional LADRC. On this basis, a new state variable is introduced to observe the differential of the total disturbance to improve its rapidity; Then a lead-lag correction link is connected on the total disturbance observation channel to suppress the problem of high-frequency noise amplification. Finally, the Bode diagram is used to analyze the performance indicators of the improved LADRC. The simulation results show that, compared with the traditional LADRC, the control strategy in this paper reduces the bus voltage amplitude fluctuation by 63%, the adjustment time by 59%, and the inductor current ripple by 66%, which is more superior to suppressing the DC bus voltage fluctuation.